2018
DOI: 10.1016/j.ram.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of toxigenic Clostridioides [Clostridium] difficile : Usefulness of two commercially available enzyme immunoassays and a PCR assay on stool samples and stool isolates

Abstract: The best laboratory diagnostic approach to detect Clostridioides [Clostridium] difficile infection (CDI) is a subject of ongoing debate. With the aim of evaluating four laboratory diagnostic methods, 250 unformed stools from patients with suspected CDI submitted to nine medical center laboratories from November 2010 to December 2011, were studied using: (1) an immunochromatographic rapid assay test that combines the qualitative determination of glutamate dehydrogenase (GDH) plus toxins A and B (QAB), the CDIFF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Although this sample was included as a false-positive result for the ELISA and GDH tests, it is more likely to be a failed growth of the isolate in the medium used in the TC protocol [9,14]. The performance of the GDH detection seen in the two commercial tests corroborates previous studies that reported the usefulness of this method as a screening test for the diagnosis of CDI [2,[15][16][17][18]. Interestingly, the similarities between the results obtained by these lateral flow tests demonstrate a very high concordance between the tests, with a K value of 0.975 (95% CI 0.926-1.000) [13].…”
supporting
confidence: 80%
“…Although this sample was included as a false-positive result for the ELISA and GDH tests, it is more likely to be a failed growth of the isolate in the medium used in the TC protocol [9,14]. The performance of the GDH detection seen in the two commercial tests corroborates previous studies that reported the usefulness of this method as a screening test for the diagnosis of CDI [2,[15][16][17][18]. Interestingly, the similarities between the results obtained by these lateral flow tests demonstrate a very high concordance between the tests, with a K value of 0.975 (95% CI 0.926-1.000) [13].…”
supporting
confidence: 80%
“…Genomic DNA was extracted from pure colonies of C. difficile isolates using the boiling method as described previously (Legaria et al 2018 ; Abbasi Montazeri et al 2020 ). Also, DNA was extracted directly from stool specimens using the QIAamp DNA Stool Minikit kit (QIAGEN, Hiden, Germany), according to the manufacturer's recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…Also, DNA was extracted directly from stool specimens using the QIAamp DNA Stool Minikit kit (QIAGEN, Hiden, Germany), according to the manufacturer's recommendations. The concentration and purity of extracted DNA were measured using a NanoDrop spectrophotometry (Thermo Scientific, Waltham, MA, USA) at 260 nm (Legaria et al 2018 ; Abbasi Montazeri et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…After isolation in CCFA medium, the presence of C. difficile was confirmed by gram stain, colony morphology, and detection of “horse-barn” odor. 16…”
Section: Methodsmentioning
confidence: 99%
“…After isolation in CCFA medium, the presence of C. difficile was confirmed by gram stain, colony morphology, and detection of "horse-barn" odor. 16 Molecular methods: DNA extraction: Each isolated strain from cultures was transferred with an inoculating loop into a 1.5 mL microcentrifuge tube containing 200 mL of sterile PBS buffer, and bacterial DNA was extracted using the QIAamp kit (Qiagen, Germany), according to the manufacturer's instructions.…”
Section: Toxigenic Culturementioning
confidence: 99%